2022
DOI: 10.1142/s0218348x22500554
|View full text |Cite
|
Sign up to set email alerts
|

On the Hitting Probabilities of Limsup Random Fractals

Abstract: Let [Formula: see text] be a limsup random fractal with indices [Formula: see text] and [Formula: see text] on [Formula: see text]. We determine the hitting probability [Formula: see text] for any analytic set [Formula: see text] with the condition [Formula: see text], where [Formula: see text] denotes the Hausdorff dimension. This extends the correspondence of Khoshnevisan et al.1 by relaxing the condition that the probability [Formula: see text] of choosing each dyadic hyper-cube is homogeneous and [Formula:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…We can also use the hitting probability of limsup random fractals to get the estimation on Hausdorff dimension in Corollary 4.1. For instance, let A be a limsup random fratcal in T with γ 1 = γ 2 < 1, δ = 0, and if P n (Q) is independent of Q, Khoshnevisan, Peres and Xiao [17] showed that dim H A = 1−γ 1 a.s. For more related research, see [13,15].…”
Section: Limsup Random Fractalsmentioning
confidence: 99%
“…We can also use the hitting probability of limsup random fractals to get the estimation on Hausdorff dimension in Corollary 4.1. For instance, let A be a limsup random fratcal in T with γ 1 = γ 2 < 1, δ = 0, and if P n (Q) is independent of Q, Khoshnevisan, Peres and Xiao [17] showed that dim H A = 1−γ 1 a.s. For more related research, see [13,15].…”
Section: Limsup Random Fractalsmentioning
confidence: 99%